ChemInform Abstract: Helical Phosphorus Derivatives: Synthesis and Applications. Issue 46 (27th October 2016) - Virieux, David; Sevrain, Nicolas; Ayad, Tahar; Pirat, Jean‐Luc
Abstract: Review: 81 refs.